Diamond Patterns: Cumulative Cornsweet Effects and Motion-Induced Brightening. (June 2018) - Cavanagh, Patrick; Anstis, Stuart
A Cornsweet edge creates the perception of a step in surface lightness between two adjacent regions of identical mean luminance due to a gradient on both sides. We might imagine that in a concatenated set of these gradients, the lightness steps would accumulate, but they do not. However, a diamond pattern, with each diamond filled with an identical luminance gradient does give a cumulative Cornsweet effect. Here, we offer an illumination explanation for why the cumulative effect is visible in the diamonds but not in the basic ramp grating and we demonstrate that when the diamonds drift, they produce a strong brightening effect (depending on the direction of the motion) and a dimming aftereffect. These effects are consistent with the local luminance gradients and not with the global lightness shift of the cumulative Cornsweet effect.